2017
DOI: 10.1016/j.cell.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Human Gut Microbiota for Immunomodulatory Organisms

Abstract: Within the human gut reside diverse microbes coexisting with the host in a mutually advantageous relationship. Evidence has revealed the pivotal role of the gut microbiota in shaping the immune system. To date, only a few of these microbes have been shown to modulate specific immune parameters. Herein, we broadly identify the immunomodulatory effects of phylogenetically diverse human gut microbes. We monocolonized mice with each of 53 individual bacterial species and systematically analyzed host immunologic ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
539
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 602 publications
(563 citation statements)
references
References 57 publications
17
539
0
7
Order By: Relevance
“…Although commensal microbes are known to be required for induction of Reg3γ expression 17 , few specific organisms have been defined. In our recently published comprehensive analysis of the immunomodulatory capacity of taxonomically diverse commensal microbes, none of 28 bacteria assessed for small-intestinal expression of Reg3γ caused significant induction 18 . We previously showed that HMb mice have ileal levels of Reg3γ expression similar to those in GF mice and lower than those in MMb mice 12 .…”
Section: Main Textmentioning
confidence: 99%
“…Although commensal microbes are known to be required for induction of Reg3γ expression 17 , few specific organisms have been defined. In our recently published comprehensive analysis of the immunomodulatory capacity of taxonomically diverse commensal microbes, none of 28 bacteria assessed for small-intestinal expression of Reg3γ caused significant induction 18 . We previously showed that HMb mice have ileal levels of Reg3γ expression similar to those in GF mice and lower than those in MMb mice 12 .…”
Section: Main Textmentioning
confidence: 99%
“…Bacterial dihydrolipoamide acetyltransferase drives Th17 cells. Sensing receptor interactions with the bacterial surface layer (S-layer) stimulate intestinal DCs, leading to T cell activation (31)(32)(33)(34). Activated T cells, in general, and antigen-specific Th17 cells, in particular, are tightly controlled by gut commensals, including segmented filamentous bacteria (SFB) (35,36) along with regulated cytokines (e.g., IL-6, TGF-β, IL-1β) (37).…”
Section: Characterization Of P Uf1 Bacteriummentioning
confidence: 99%
“…Recent studies analysing the effects of introduced bacteria on the host suggest that several commensals have generic and redundant effects on immunity (Geva‐Zatorsky et al ., 2017). However, these effects may change in the presence of an intact microbial community and likely interact with diet and host health (Maldonado‐Gómez et al ., 2016).…”
mentioning
confidence: 99%